Pengaruh Environmental Performance dan Keputusan Investasi terhadap Nilai Perusahaan dengan Financial Performance sebagai Pemediasi - Yeyen Yustiani; Riris Rotua Sitorus (Jurnal Riset Akuntansi Politala, 2026)
Using the mining sector industry listed on the IDX for the period 2019-2022, the purpose of this study is to investigate how environmental performance and investment decisions affect firm value, with financial performance as an intervening or mediating variable. Environmental performance and investment decisions are used as independent variables, company value as a related variable, and financial performance is applied as a mediating or intervening variable. This research uses ten companies as the population and forty company data as the research sample. The test results of this study resulted in environmental performance and investment decisions have a significant effect on financial performance and environmental performance, investment decisions and financial performance both have a significant effect on firm value. The financial performance variable proxied by Return on Asset is unable to mediate the effect of environmental performance on firm value. Financial performance does not act as a mediator in the relationship between investment decisions and firm value.